Nested Games of External Democracy Promotion The United States and the Polish Liberalization 1980-1989 - Thiel, Rainer; SpringerLink (Online service) (Wiesbaden : VS Verlag für Sozialwissenschaften, 2010)
Nested Games of External Democracy Promotion develops a game theoretic model that explains how an external actor influences the strategic interaction between an authoritarian regime and a democratic opposition. In a multiple arena approach, the confrontation between regime and opposition on the domestic level is nested inside a game on the international level, at which the regime is simultaneously entangled with a democracy promotion actor. As a case study, the book formally reconstructs how United States democracy assistance influenced the Polish liberalization process between 1980 and 1989. The process tracing of its causal mechanisms is extensive and builds on data previously not recorded. With regard to Cold War history, new light is brought into U.S. American policies and strategies behind the Iron Curtain.
Regime Transitions and External Democracy Promotion -- The International Dimension of Regime Change -- Strategic Transitions -- Nested Games of External Influence on Strategic Regime Transition -- Methodology -- U.S. Democracy Assistance in the Polish Liberalization Process, 1980-1989 -- Correspondence between Theory and Facts -- Conclusion.
Keywords: Political science; International relations; Political Science and International Relations; Political Science; International Relations; Electronic books